THE INFLUENCE OF THE ORIENTATION AND STRENGTH OF THE EXTERNAL MAGNETIC FIELD ON THE CORROSION PROCESS OF FERROMAGNETIC THIN FILMS OF IRON - A. S. Naboko; S. S. Maklakov; S. A. Maklakov; I. A. Ryzhikov; R. H. Akchurin; M. V. Sedova (Тонкие химические технологии)
The results of a study on the rate of galvanic corrosion of thin ferromagnetic iron films in an external uniform magnetic field are presented. It is shown that the direction of the external magnetic field has different influence on the corrosion rate in the presence of a magnetic field. The shape of the micro-relief surface iron film subjected to a short-term treatment with a solution of acetic acid was studied. The relief is formed on the surface due to the heterogeneity of the corrosion rate on the surface of the film. Areas of high corrosion rates correspond to areas of the domain boundaries of the ferromagnetic film. When the orientation of the external magnetic field is changed, the domain structure changes, which is reflected in the change of the average rate of corrosion.